Evaluasi PJOK Model Kirkpatrick Untuk Peningkatan Hasil Belajar dan Sikap Kebiasaan Baru Pasca Pandemi di Sekolah Dasar - Suroso Suroso; Bambang Ismanto; Suhartono Suhartono (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2023)
This study aimed to provide an overview regarding the evaluation of Kirkpatrick's model in Physical Education. A descriptive qualitative was conducted in this research. The sample was 17 students from fourth grade as the control class and 24 students from the fifth grade of Elementary School. The data in this study were collected using a questionnaire. Student responses to Kirkpatrick's assessment model and the scoring rubric used were very positive, as proved by the results of students' independent work. The students performed well in academic evaluations. In the assessment, assessors can prioritize the direction to be achieved, student targets, and measurement columns. Students enthusiastically express all the possibilities that exist within them. The success of each program implemented is very dependent on the responses and results of students who experience increased knowledge, skills, and attitudes of students in realizing the final task given by the teacher. It appears that the results for the control class were 94.12% of students able to take part in the PJOK learning process in the good category and in the impact class 91.67% of students were able to take part in the PJOK learning process in the good category. In conclusion, this study indicated that using the Kirkpatrick evaluation model in Physical Education subject during the learning process had been very and can explore all students’ competence.